2021
DOI: 10.1039/d1ma00100k
|View full text |Cite
|
Sign up to set email alerts
|

Unique “posture” of rose Bengal for fabricating personal protective equipment with enhanced daylight-induced biocidal efficiency

Abstract: RB captured by super-adsorptive cotton achieves enhanced biocidal activity by alleviating aggregation-caused self-quenching and modulating the photoreaction of RB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
0
15
0
2
Order By: Relevance
“…Because the dimerization of CV inhibits electron or energy transfer by self-quenching photoexcited CV, it is unfavorable to ROS generation [16] , [30] . However, the SAPC filter showed a monomeric band at 590 nm, the same as that exhibited by the solution form, which indicates dimerization inhibition [31] . It is attributable to the improved dispersity of the CV dye in the SAS matrix, caused by electrostatic interaction between cationic CV molecules and SAS matrix via hydrogen bonding [32] .…”
Section: Resultsmentioning
confidence: 77%
“…Because the dimerization of CV inhibits electron or energy transfer by self-quenching photoexcited CV, it is unfavorable to ROS generation [16] , [30] . However, the SAPC filter showed a monomeric band at 590 nm, the same as that exhibited by the solution form, which indicates dimerization inhibition [31] . It is attributable to the improved dispersity of the CV dye in the SAS matrix, caused by electrostatic interaction between cationic CV molecules and SAS matrix via hydrogen bonding [32] .…”
Section: Resultsmentioning
confidence: 77%
“…Experimental results showed that mixing such supernatant with the pathogens did not induce any killing effect, implying that the release of copper cations is not the major mechanism of antimicrobial action for the CuI-coated cotton fabrics. Even though ROS generation was reported before to account for the antimicrobial property of CuI and some other materials, , we speculate that it is not the main mechanism for the CuI-coated cotton fabrics, because (i) the presence of ROS in the CuI suspension was not detected with multiple attempts using 1,3-diphenylisobenzofuran (DPBF) as the probe, (ii) the CuI-coated fabrics need much shorter contact time to inactivate pathogens, compared to that in previous examples, , and (iii) the pathogen inactivation effect can be generally observed for both metabolically active ( e.g. , bacteria, fungi) and inactive pathogens ( e.g.…”
Section: Resultsmentioning
confidence: 80%
“…The antibacterial assays were performed according to a standard method of the AATCC 100 Test Method with modifications. Specifically, in a typical antibacterial test, the bacterial culture solution underwent two cycles of centrifugation (5000 rpm, 8 min) with washing by 10 mL of cold sterile phosphate-buffered saline (PBS). Then, 20 mL of PBS was mixed with bacterial precipitates to form the final bacterial culture suspension.…”
Section: Methodsmentioning
confidence: 99%